A Descriptive Overview of Patient Visit Patterns at the Joint Medical Practice Tenggarong. - Ayu Sri Mega Astuti; Ratno Adrianto; Nur Rohmah (Mulawarman International Conference on Tropical Public Health, 2025)
Backgorund : A joint medical practice is a modern health service model that integrates several types of medical services such as general practitioners, dentists, and ophthalmologists within a single facility. This model aims to improve efficiency, accessibility, and quality of care for the community, especially for individuals with limited time due to work or study. Objective : Describe the general pattern of patient. Viewed from the type of service visited, time of visit, age group, gender, education level and monthly distribution. Methods : A descriptive observational study with a retrospective approach using secondary data from patient medical records. The population included all patient visits recorded from Jan-June 2025, totaling 593 visits. Data were analyzed univariately using frequency and percentage. Results : The study showed that the highest number of visits was to dentists (48.7%), ophthalmologists (34.4%), general practitioners (16.9%). Most patients visited during evening hours (43.3%), the majority belonged to the productive age group of 21–35 years (37.5%). In terms of occupation, housewives (22.3%), employees (19.9%), private workers (19.4%) dominated. Most patients had a senior high school education (51.4%), were male (53.5%). Monthly distribution indicated an increase in patient visits, peaking in May (20.7%) and lowest in January (9.1%). Conclussion : The pattern of patient visits at Apotek Sejiwa Joint Medical Practice shows an upward trend with a predominance of productive-age patients seeking dental and eye care services. The evening time became the most preferred period for visits. This indicates that the joint medical practice model is an effective and adaptive form of healthcare delivery.